Integrated morphological and physiological plasticity of root for improved seedling growth in Cunninghamia lanceolata and Schima superba under nitrogen deficiency and different NH4+-N to NO3−-N ratio - Wang, Yan-Ru; Quan, Xiao-Qiang; Li, Xiao-Yu; Cheng, Cong; Yu, Jia-Xiang; Tang, Xing-Hao; Wu, Peng-Fei; Ma, Xiang-Qing; Yan, Xiao-Li (Frontiers in Plant Science, 2025)
ContextRoot plasticity is an important physiological mechanism for trees to adapt to nitrogen (N) deficiency and the unequal distribution of ammonium nitrogen (NH4+-N) and nitrate nitrogen (NO3−-N) for promoting growth. However, the response of root plasticity in Cunninghamia lanceolata and Schima superba remains unclear.MethodsA pot experiment with C. lanceolata and S. superba compared N deficiency (0.5 mmol L-¹) and normal N (2.0 mmol L-¹) under five NH4+-N to NO3--N ratios (10:0, 8:2, 5:5, 2:8, 0:10). Root morphological and physiological traits and seedling growth were investigated.ResultsUnder N deficiency, C. lanceolata showed significantly higher total root surface (TRS) and total root volume (TRV) at higher NO3−-N concentrations, although the roots were shorter and thicker than normal N. It also showed an increased root tissue density (RTD) while specific root length (SRL) and specific root surface area (SRS) decreased. In contrast, roots of S. superba elongated at higher NH4+-N concentrations, with an increase in TRS, TRV, SRL, and SRS, while RTD decreased. Different N supply treatments significantly affected N-metabolism enzyme activities in the roots of both species. The root biomass of C. lanceolata and S. superba increased compared with normal N supply level, and the relatively high NH4+-N concentrations favored aboveground growth in both species. Principal component and correlation analysis revealed that there were differences in the response of C. lanceolata and S. superba to different N supply treatments.ConclusionAppropriately increasing the application of NH4+-N under N-deficient conditions promotes the growth of C. lanceolata and S. superba.